The impact of transportation development on land price differences between cities: Widening or narrowing?—A case study based on the provincial level of Mainland China. (7th February 2022) - Li, Tianshu; Chen, Zhigang
Abstract: Exploring the impact of transportation development on land price differences between cities is of great significance to help guide the optimal allocation of land resources and promote the coordinated and balanced development of regions. This paper first discusses how regional transportation development influences land price differences between cities at a theoretical level. Then, by taking 26 provincial regions in the Chinese Mainland as research units, the specific effects of provincial transportation development on land price differences between cities are examined empirically by constructing econometric models. The results show that: (a) in recent years, the price of urban land in China has increased significantly, and the land price differences between cities are increasing in most provinces; and (b) provincial transportation development has a narrowing effect on land price differences between cities, and the spatial spillover effect brought by transportation development deserves attention. In the future, the role of transportation development in narrowing regional land price differences should be taken into consideration to promote the balanced development of the land market and the coordinated development of regions.